PERFORMANCE ANALYSIS OF LITHIUM-ION BATTERY CHARGER SYSTEM - Samosir, Daniel Junaedi; Satria, Beni; Aryza, Solly (Bahasa Indonesia, 2025)
Lithium-ion battery chargers have become one of the important components in various modern applications, especially in electronic devices and electric vehicles. This study aims to analyze the performance of a lithium-ion battery charger system in terms of charging efficiency, voltage stability, charging current, and safety during the charging process. In this study, the constant current (CC) and constant voltage (CV) charging methods are used as the basis for analyzing the performance of the charging system. Data were taken through real-time measurements of key parameters such as charging time, temperature changes, and power efficiency under various charging conditions. The results showed that the performance of the charger system was influenced by several factors, including the stability of the power supply and heat management during the charging process. Tests also showed that the CC-CV mode was able to maintain battery safety by preventing overcharge, and provided better charging efficiency at certain voltage ranges. Through this study, it is expected to provide a better understanding of the optimization of lithium-ion battery charger systems to improve overall battery performance and life.